Dynamics of development of spheres of life of ethnic Germans of Kazakhstan (Results of a sociological study) (International relations and international law Journal, 2019)
The subject of this study is the analysis of the state and dynamics of development of the main spheres of life of ethnic Germans in Kazakhstan, as well as the analysis and assessment of the effectiveness of public associations of Germans in Kazakhstan. The article discusses the functioning of the German diaspora in multinational Kazakhstan. In order to achieve the goal and solve the problem, monitoring and analysis of the development prospects and activities of the German cultural and ethnic communities of Kazakhstan are carried out. The authors conclude that the National Cultural Centers of the German Diaspora in Kazakhstan, various German firms actively contribute to the development of German culture, the German language, etc. They have at their disposal individual media (radio, print media, Internet portals). The effective work of national associations contributes to the growth of the integration potential of members of the German diaspora, removes cultural barriers, creates the conditions for international dialogue and mutual understanding. The process of formation of a single Kazakhstani culture involves the development of the culture of all ethnic groups. As for the national cultural centers, it is necessary to state the fact of their direct interaction with the Assembly of the People of Kazakhstan. The delegates of the Assembly, as members of national cultural centers, actively contribute to the implementation of decisions adopted at the sessions of the Assembly.Key words: monitoring, questioning, ethnic group, ethnic Germans, public associations.